(untitled) (Linguostylistic Studies, 2014)
This article attempts to analyse specific functioning of syntactically indecomposable (lexical) phrases, important elements of Ukrainian nominative system, in Lesya Ukrainka’s works. Lexical, or syntactically indecomposable, phrases occupy a prominent place in the sphere of nominative derivation of Ukrainian language. Their semantic and structural specificity expresses Lesya Ukrainka’s personal style, reflects general trends of modern Ukrainian language. Lexical phrases with the richest semantic characteristics, that may denote temporal concepts, definitions from various fields of science, culture, social life, production, function as the names of geographical features, political groups of different status, persons, objects or state phrases from the Bible, literature, folklore, mythology and other areas have been denoted in the article. It has been noted that models of lexical phrases, which are a combination of two or three nouns, adjectives and nouns are efficient. Key words: nominative system, derivation, syntactically indecomposable phrases, lexical phrases. References